Identifying discordance between senior physicians and trainees on the root cause of ED revisits. Issue 12 (11th August 2017) - Goldman, Michael P; Monuteaux, Michael C; Perron, Catherine; Bachur, Richard G
Abstract : Objective: Analysis of 72-hour ED revisits is a common emergency medicine quality assurance (QA) practice. Our aim was to compare the perceived root cause for 72-hour ED revisits between senior physicians (attendings) and trainees. We proposed that discordance in perception of why the revisit occurred would guide improvements in 72-hour revisits QA and elucidate innovative educational opportunities. Methods: Questionnaire-based observational study conducted in an urban academic paediatric ED. Treating attendings and trainees independently completed questionnaires on revisit cases. The primary outcome was the revisit's perceived root cause, dichotomised into 'potential medical deficiency' or 'not potential medical deficiency'. Discordance between provider pairs was measured, stratified by revisit disposition. Results: During the study period, 31 630 patients were treated in the ED, 559 returned within 72 hours and 218 met inclusion criteria for paired analysis. The proportion of cases assigned 'potential medical deficiency' by the attending and trainee was 13% and 9%, respectively. Discordance in the dichotomised root cause between attendings and trainees was 17% (38/218, 95% CI 12% to 22%). Revisit cases requiring admission revealed attending-trainee discordance of 25% (23/92, 95% CI 16% to 34%). Conclusions: Attendings and trainees frequently disagree on whether a potential medical deficiency was the root cause for an ED revisit, with more disagreement noted for cases requiring admission. These findings support the premise that there may be opportunities to improve 72-hour revisits QA systems through trainee integration. Finally, reuniting attending-trainee pairs around revisit cases may be a novel educational opportunity.